The Correlation Between Early Breastfeeding Initiation with The Increase of Newborn’s Body Temperature at Rumah Sehat Cinta Mama Clinic of Tebing Tinggi City in 2017 - Lusiana Gultom (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Abstract Newborn mortality in Indonesia at 5 years ago is concern because neonatal mortality (0-28 days) contributes 59% of infant deaths. To address this, early initiation breastfeeding management in field of maternal and child health is increasingly encouraged in order to reduce newborn mortality. Newborns often suffer decrease in body temperature, this due to inability newborn maintain body temperature, for baby's body temperature to remain normal than early breastfeeding initiation is one effort to keep baby's body warm. The purpose of this study to determine the relationship of early breastfeeding initiation with the increase newborns body temperature in Rumah Sehat Cinta Mama Clinic Tebing Tinggi City 2017. The method of this research was quasi eksperiment with one group pretest posttest design, using primary data that direct observation to respondent. The sampling technique is total sampling its all pregnant women who have interpretations of the birth date in April - July 2017 of 30 respondents. The reasult of this research has been showing that of statistic sample pired test which a significant association between early breastfeeding initiation and the increase in body temperature of newborns (? value = 0,000 <0.05). Expected to the Rumah Sehat Cinta Mama Clinic, especially midwife health personnel to improve the quality and quantity of early breastfeeding initiation and involve the husband or family to support implementation of early breastfeeding initiation so as to reduce the newborn mortality rate and the achievement the target of Infant Baby Mortality Rate which the Ministry of Health has established.